3-Hydroxy-3-methylglutaryl-coenzyme A lyase deficiency: Clinical presentation and outcome in a series of 37 patients - Grünert, Sarah Catharina; Schlatter, Sonja Marina; Schmitt, Robert Niklas; Gemperle-Britschgi, Corinne; Mrázová, Lenka; Balcı, Mehmet Cihan; Bischof, Felix; Çoker, Mahmut; Das, Anibh M; Demirkol, Mübeccel; de Vries, Maaike; Gökçay, Gülden; et al. (Molecular genetics and metabolism, 2017)
3-Hydroxy-3-methylglutaryl-coenzyme A lyase deficiency (HMGCLD) is a rare inborn error of ketone body synthesis and leucine degradation, caused by mutations in the HMGCL gene. In order to obtain a comprehensive view on this disease, we have collected clinical and biochemical data as well as information on HMGCL mutations of 37 patients (35 families) from metabolic centers in Belgium, Germany, The Netherlands, Switzerland, and Turkey. All patients were symptomatic at some stage with 94% presenting with an acute metabolic decompensation. In 50% of the patients, the disorder manifested neonatally, mostly within the first days of life. Only 8% of patients presented after one year of age. Six patients died prior to data collection. Long-term neurological complications were common. Half of the patients had a normal cognitive development while the remainder showed psychomotor deficits. We identified seven novel HMGCL mutations. In agreement with previous reports, no clear genotype-phenotype correlation could be found. This is the largest cohort of HMGCLD patients reported so far, demonstrating that HMGCLD is a potentially life-threatening disease with variable clinical outcome. Our findings suggest that the clinical course of HMGCLD cannot be predicted accurately from HMGCL genotype. The overall outcome in HMGCLD appears limited, thus rendering early diagnosis and strict avoidance of metabolic crises important.
Keywords: Organic aciduria; Ketone body synthesis; Oxo-Acid-Lyases; Nizozemsko; Ketone Bodies; Enzyme activity; Leucine degradation; lidé; mladiství; Turecko; Adult; Leucine; Germany; Patient Outcome Assessment; vrozené poruchy metabolismu aminokyselin; Switzerland; Acetyl-CoA C-Acetyltransferase; Turkey; Infant; Female; dítě; acetyl-CoA-C-acetyltransferasa; hodnocení výsledků pacienta; Netherlands; Mutation; Ketogenesis; Adolescent; Humans; lyasy oxokyselin; mutace; předškolní dítě; mastné kyseliny; Child, Preschool; Švýcarsko; mužské pohlaví; mladý dospělý; genetické asociační studie; Belgium; ženské pohlaví; ketolátky; leucin; Young Adult; Německo; Fatty Acids; Genetic Association Studies; Male; Child; dospělí; Belgie; Amino Acid Metabolism, Inborn Errors; Fatty acid metabolism; kojenec